The Role Of Thein Improving The Conseleempaty In Family Members - Heppi Sasmita, Neviyarni S, Yarmis Syukur (Journal of Education and Teaching Learning, 2021)
Every family wants harmony in the family. Awareness of the role and function of accepting circumstances and existence is a very strong foundation in running a household. In realizing a harmonious household, of course there are problems that must be resolved immediately so that family harmony is maintained and realized. The family has an important role in the success of the child, remembering that most of the time in the child's daily life with the family, the family is the first community for the child to interact. But in this digital era, many people of all ages have really changed. Changing to be fast paced, but also decreasing the harmony that has been established in the family, this can be seen by the reduced love, cooperation and sharing in the family because they are busy with their respective activities, especially when dealing with gadgets so that harmony in the family is reduced. The role of school counselors is indispensable in forming empathy for family members to achieve household harmony by using family counseling, which is used as an intervention process for problems that interfere with family harmony. Family counseling seeks to build closer bonds, individuals who are able to control emotions, and families who always have good communication in realizing family harmony.